FROM KNOWLEDGE TO PROSPERITY: ASSESSING THE RELATIONSHIP BETWEEN KNOWLEDGE ECONOMY AND LIVING STANDARDS - Ayub Islam; Zahid Ali; Muhammad Ghulam Shabeer (International Journal of Contemporary Issues in Social Sciences, 2024)
Improving the standard of living is the primary objective of all societies, as it reflects the overall quality of life. This research investigates the rationale behind living standards by examining the knowledge economy. The study utilises secondary data from world development indicators for selected economies, covering 2000 to 2023. Appendix (A) contains the catalogue of nations chosen for this study. The independent variables comprise knowledge capital, Education, and technology (represented by High-technology exports). Additional variables include health, Foreign direct investment (FDI), life expectancy, gross capital formation, labour force participation and inflation. To address the research objective, a model investigates the influence of knowledge capital variables on per capita income, which indicates living standards.The study employs a log-log model, with variables transformed using natural logarithms. The model was evaluated using panel-corrected standard error to address the limitations of ordinary least squares (OLS) and account for potential non-spherical errors, heteroskedasticity, and correlation. The findings indicate that the explanatory variables have a positive influence on the standard of living.